Optimization of aquaculture sustainability through ecological intensification in China. (10th January 2022) - Dong, Shuang‐lin; Dong, Yun‐wei; Cao, Ling; Verreth, Johan; Olsen, Yngvar; Liu, Wen‐jing; Fang, Qi‐zhi; Zhou, Yan‐gen; Li, Li; Li, Jing‐yu; Mu, Yong‐tong; Sorgeloos, Patrick
Abstract: As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.